CHARACTERISATION OF ODAYERI SANITARY LANDFILL LEACHATE - Akkaya, Ebru; Demir, Ahmet; Varank, Gamze (YILDIZ TECHNICAL UNIV, 2011)
Odayeri sanitary landfill has been operated since 1995 by ISTAC A. S. From 1995 to 2008, 45 million tonnes of waste has been disposed in the site. According to 2008 year data, the solid waste amount disposed in the site and leachate formed in a day are 12000 m(3) and 2100 m(3) respectively. Amount of formed leachate for Komurcuoda sanitary lanfill is 1000m(3). Characteristics of Odayeri landfill leachate has been studied by many researchers. It is determined from many studies that COD of Odayeri and Komurcuoda leachate are 70000 and 50000 mg/L respectively. Today this value is 10000 mg/L for both landfill. This point out that, landfills is old aged. In 1995 BOD of Odayeri and Komurcuoda are 30000 and 40000 mg/l, TKN values are 1000 and 1800 mg/L, pH values are 6 and 6,5 respectively. Today BOD, TKN and pH of both landfills are approximately 5000 mg(L, 2500 mg/L and 8 respectively. In this work, studies about Kemerburgaz-Odayeri landfill leachate characterization and treatment collected 1000 day period. Characterization of leachate is determined and the results are statistically evaluated.
Keywords: Leachate; Leachate treatment; characterization; Engineering